Vienna as one of Paul Celan’s first publication places - Havryliv, Tymofiy (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
This article is focused on the publications of the German-speaking poet Paul Celan, who comes from Černivci in Bukovina, during his stay in Vienna. “Viennese” publications are treated in the context of the poet’s stay in Vienna and in the context of his oeuvre. Inasmuch as the period before Celan’s stay in Vienna found its way into his early work, it is also taken into account. Although the Vienna period marks the end of the first period of Celan’s life, it is anticipated and influenced by the events that preceded it as well as by the cultural and historical situation. With the arrival in Vienna, the dilemma of the German mother language versus the murderer’s language was sealed once and for all. The themes of the mainly lyrical texts published during the stay in Vienna will then be further developed. The Shoah experience, which was already discussed in early lyrical work, brought about a radical rethinking of the role of poetry and its formal parameters.